2011
DOI: 10.1155/2011/741051
|View full text |Cite
|
Sign up to set email alerts
|

Different Transcriptional Profiles of Human Monocyte-Derived Dendritic Cells Infected with Distinct Strains ofMycobacterium tuberculosisandMycobacterium bovisBacillus Calmette-Guérin

Abstract: In order to analyze dendritic cells (DCs) activation following infection with different mycobacterial strains, we studied the expression profiles of 165 genes of human monocyte-derived DCs infected with H37Rv, a virulent Mycobacterium tuberculosis (MTB) laboratory strain, CMT97, a clinical MTB isolate, Mycobacterium bovis bacillus Calmette-Guérin (BCG), Aventis Pasteur, and BCG Japan, both employed as vaccine against tuberculosis. The analysis of the gene expression reveals that, despite a set of genes similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
(54 reference statements)
1
13
1
1
Order By: Relevance
“…This indicates that they possess the ability to respond to the above chemokines and migrate accordingly; further highlighting that this inhibition is exclusive to M. tuberculosis and is suggestive of a mechanism independent of CCR7. This is in contrast to reports of mycobacteria inhibiting chemotaxis of DCs through a block in the up‐regulation of CCR7 . Our data also suggest a mechanism by which a loss of surface‐expressed integrins impacts migration.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates that they possess the ability to respond to the above chemokines and migrate accordingly; further highlighting that this inhibition is exclusive to M. tuberculosis and is suggestive of a mechanism independent of CCR7. This is in contrast to reports of mycobacteria inhibiting chemotaxis of DCs through a block in the up‐regulation of CCR7 . Our data also suggest a mechanism by which a loss of surface‐expressed integrins impacts migration.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the opportune response of host to Mycobacterium tuberculosis and the antigens they confront are still unclear. Simultaneously, the innate immune response to pathogenic bacteria and the subsequent adaptive immune response to eliminate the pathogens which can protect the host from pathogenic bacterial invasion have not been expound systematically [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, this is the first demonstration of a significant difference in the in‐vitro infectivity of human DCs by Lm strains differing by their virulence. Recently, it was reported that DCs control the intracellular growth of mycobacteria strains differently, suggesting variability in the cell‐to‐cell spread outcome during the first step of infection [26].…”
Section: Discussionmentioning
confidence: 99%
“…An asterisk indicates a statistically significant difference between uninfected and LPS-matured DCs (P < 0·05); **statistically significant difference between uninfected and IFN-g/LPS-matured DCs (P < 0·05). growth of mycobacteria strains differently, suggesting variability in the cell-to-cell spread outcome during the first step of infection [26].…”
Section: Discussionmentioning
confidence: 99%